Implementation of Regional Regulation N0 15 Of 2015 In Majene Regency in The Effectiveness Of Islamic Law - Reski Amaliah; Asnawi Asnawi (Indonesia Prime, 2022)
The main problem of this paper is how to implement Majene Regency Regional Regulation Number 19 of 2015 in the Permit for the Establishment and Arrangement of Self-Service Layouts in Majene Regency from the Perspective of Islamic Law. This type of research is classified as field research with a syar'i normative theological approach and an empirical juridical normative juridical approach. The results of this study show that the application of Majene Regency Regional Regulation number 19 of 2015 in the application of supermarket establishment permits in Majene Regency shows that the application of permits setting up a supermarket in Majene has been implemented, but the application for an establishment permit has not been maximized because there are still violations and points that have not been carried out in accordance with the bylaws In view of Islamic law, protection of the empowerment of small businesses and traditional markets are activities that renew the development of human life in order to benefit from ulil amri from the decision of the Government, in accordance with Maqāṣid al-Shari'ah.